Flexural behavior and analysis of reinforced concrete beams made of recycled PET waste concrete. (30th November 2017) - Mohammed, Azad A.
Graphical abstract: Highlights: Up to 15% well graded PET waste shredded particles can be accurately added to concrete for reinforced concrete beams. Grading of PET waste particles is not helpful to control the reduction in compressive strength. Lightly reinforced concrete beams containing PET waste particles behave like the normal beam. Ultimate load capacity of the beam is moderately reduced as a result of PET waste addition. Analysis of concrete section containing PET waste can be made following the procedure for normal beams. Abstract: This paper describes results of testing and analysis of reinforced concrete beams contained PET waste particles. The beams were lightly reinforced with steel rebar and designed to fail in flexure. Test results showed that as a result of using PET waste shredded particles in concrete as sand replacement there is a reduction in compressive strength in the range of 12–21%. Properties of stiffness and mode of failure for recycled PET waste reinforced concrete are almost identical to those of normal beams. Ultimate load capacity was reduced moderately, and load-deflection response was slightly changed as a result of using PET waste particles up to 15%. Regression analysis was made for developing equations for calculating compressive strength and maximum compressive strain of concrete containing PET waste. Later, analysis was made for calculating ultimate moment capacity of under reinforced concrete section. Making a comparison with the test data showed that the predictions of moment capacity are accurate. The difference between calculated moment based on test and that based on calculated compressive strength was found to be not important. It is concluded that up to 15% well graded PET waste can be added safely to produce this type of recycled reinforced concrete beams for structural applications.